The Safety, Pharmacokinetics, and Nervous System Effects of Two Natural Sources of Caffeine in Healthy Adult Males. Issue 5 (20th June 2016) - Krieger, DR; Kalman, DS; Feldman, S; Arnillas, L; Goldberg, D; Gisbert, O; Nader, S
Abstract : This double‐blind crossover clinical trial randomized 12 adult males to receive 200 mg of caffeine from a green coffee extract, a guayusa leaf extract, and a synthetic control to compare their safety, absorption, and effect on neurotransmitters. The results showed no statistically significant changes in blood pressure or heart rate from baseline to 120 min postdose of each natural source compared with changes from baseline in the control ( 0.094 < = P < = 0.910 ). The ratios of Cmax, AUC0‐4, and AUC0‐∞ of each natural source to the control were bioequivalent by US Food and Drug Administration standards (90% CI within 80–125%). The guayusa leaf extract stimulated a significantly lower increase in epinephrine compared with the control (+0.5 vs. +2.78 μg/gCr, P = 0.04 ), while the green coffee extract provoked an increase in epinephrine similar to the control (+3.21 vs. +2.78 μg/gCr, P = 0.569 ). Implications for future clinical research are discussed.